Effect of the structure of the board of directors on cash holdings of publicly traded companies - Ferreira, Marília Paranaíba; Vicente, Ernesto Fernando Rodrigues (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
The board of directors is an important internal mechanism of corporate governance, since its primary function is to monitor the actions of the executive board, which reduces possible managerial failures. In this sense, this study aims to verify the effect of the structure of the board of directors on cash holdings of publicly traded companies in the period between 2010 and 2018. The data were analyzed by multiple and quantile regressions and the results showed that the board independence, CEO duality and the board size positively affect the amount of cash by publicly traded companies.